Skin manifestations in diabetes—what is new? - Dorf, Natalia; Maciejczyk, Mateusz (Frontiers in Medicine, 2025)
Diabetes is a chronic disease with a continuously increasing prevalence worldwide. Chronic hyperglycaemia results from elevated blood glucose levels due to disturbed insulin secretion and/or action. Diabetes adversely affects the structure and function of micro- and macrovasculature, leading to the failure of various organs and tissues. Diabetes complications affect the kidneys, retina, peripheral nerves, heart, brain, muscle, and skin. Approximately 30% of diabetic patients have cutaneous manifestations, which may be the first sign of metabolic derangement. Skin manifestations strongly associated with diabetes are foot ulcers, diabetic gangrene, diabetic dermopathy, yellow palms and soles, acanthosis nigricans, bullosis diabeticorum, diabetic thick skin, scleredema diabeticorum, and necrobiosis lipoidica. Non-specific symptoms associated with diabetes include acrochordons, rubeosis faciei diabeticorum, eruptive xanthomas, acquired reactive perforating collagenosis, keratosis pilaris, pruritus, vitiligo, granuloma annulare, lichen planus, as well as bacterial and fungal infections. The prompt recognition of skin lesions can initiate early diagnostic testing and timely treatment, minimising long-term complications of diabetes. The use of specialised bioactive dressings in the treatment of diabetic wounds, as well as immunomodulatory and anti-fibrotic therapies in diabetic dermatoses, is a current treatment trend. This review summarises the recent knowledge on the pathogenesis and clinical conditions of cutaneous manifestations related to diabetes mellitus.